Analisis Pendapatan Petani Model Usahatani Terpadu Jagung-Sapi di Kecamatan Payakumbuh - Mukhlis; Riva Hendriani; Nila Sari; Raeza Firsta Wisra; Siska Fitrianti; Ulva Mohtar Lutfi (Politeknik Negeri Lampung., 2023)
This research is based on the new paradigm of agricultural development is the development of integrated farming. Agricultural development aims to optimize the utilization of natural resources and advanced technology is cheap, simple, and effective accompanied by the arrangement and development of agricultural institutions in rural areas. Integrated farming as a solution to problems in economic development. The purpose of this study is to analyze the income of farmers in the corn-cattle integrated farming model. This study uses a descriptive method, which is carried out in Lima Puluh Kota Regency, precisely in Payakumbuh District. The selection of the research area was carried out in purposive method. The study was conducted in Juli - Oktober 2022. Determination of the research sample using the snowball sampling method. Collecting data using interview method using questionnaires to obtain primary data and documentation method to obtain secondary data. The data analysis method used descriptive analysis using analysis of farm income, and using analysis of R/C ratio and profitability.The results showed that the average production amount of corn produced was 3.48 tonnes /hectare, with total revenues obtained amounting to IDR 11,327,000 and total cost of IDR 8,759,250/hectare. So, the total income obtained from corn integrated farming are IDR 2,567,750. The total revenues obtained from integrated farming of cattle farming are IDR IDR 98,441,500 with a total cost of IDR 78,910,069.57 /head. So the total income obtained from integrated farming of cattle are IDR 19,531,430.43. The value of the R/C ratio of integrated corn farming is 1.26; with a profit rate of 30.54%. Whereas, the R/C ratio for integrated cattle farming is 1.22, with a profit rate of 22.37%. The value of the R/C ratio and the profit level obtained showed that the corn-cow integrated farming model is feasible to be cultivated and developed.